Data from Smoke Particle Impact Detector (SPID) rocket instrument - Henriette Trollvik; Tinna Gunnarsdottir (DataverseNO, 2024)
It contains data from the smoke particle impact detector (SPID). SPID is a Faraday cup impact probe designed to measure nanometer-sized smoke particles, called meteoric smoke particles, in the mesosphere. These are remnants of meteors ablating in the atmosphere. The instrument was part of the G-chaser campaign launched from Andøya rocket range on the 13th of January 2019. The instrument consists of 5 girds, the two top and bottom grids with high bias voltages to shield ions and electrons. The middle plate (5th grid) is meant to measure only the smoke particles. The measurement consists of the current measured in the five grids given in ampere.